Penggunaan Informasi Keuangan untuk Memprediksi Keuangan Investasi bagi Investor di Pasar Modal - Parawiyati, Ambar woro hastuti, edi subiyantoro (IAIKAP, 2000)
The objective of this research is to text relationship of the ability financial information in prediciting the benefit of equity investment that consists of earnings and cahs flow. Financial information includes; changes, and gross profit to sales ratio. Thereason for using financial variables is based on the evidance that previous researchers used the same variables as significant indicators ofthe effect of changes in earnings and cahs flows. This research has gotten a sample of 299 financial reports, whichg were published among 1998-1994 by manufacturing firms, which quoted on the jakartastock exchange. The first hypothesis is that financial informatuon will predict the changes in earngings and cahs flow for one year or more. While the second, they are provide incremental prediction ability in the presence of cahs flow. The statistical results how that financial information is usefeful in predicting changes in earnings and cahs flow. Earnings and gross profit to sales ratio were significant in predicting changes in earnings one year ahead, but not significant for predicting cash flow. The significant variables in predictingthe changes in earnings and cash flow ahead were selling and administrative expeses and gross profit to sales ration. The tests whether earnings provide incremental predictive in the presence of cash flow, the result of statistics shows that it was not significant, haowever cash flow is a better predictor of cash flow